2014
DOI: 10.1103/physreve.89.042602
|View full text |Cite
|
Sign up to set email alerts
|

Crosslink-induced shrinkage of grafted Gaussian chains

Abstract: The statistical mechanics of polymers grafted on surfaces has been the subject of intense research activity because of many potential applications. In this paper, we analytically investigate the conformational changes caused by a single cross-link on two ideal (Gaussian) chains grafted on a rigid planar surface. Both the cross-link and the surface reduce the number of allowed configurations. In the absence of the hard substrate, the sole effect of the cross-link is a reduction in the effective Kuhn length of a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…From the methodological point of view, our work illustrates the usefulness of the Sherman-Morrison formula in extending a Gaussian theory to incorporate non-trivial features. In [28] and [29], it was used in order to describe a polymer crosslink.…”
Section: Discussion -Conclusionmentioning
confidence: 99%
“…From the methodological point of view, our work illustrates the usefulness of the Sherman-Morrison formula in extending a Gaussian theory to incorporate non-trivial features. In [28] and [29], it was used in order to describe a polymer crosslink.…”
Section: Discussion -Conclusionmentioning
confidence: 99%
“…Current and future modelling extensions focus on (i) studying the effect of chain architecture on jamming, (ii) the simulation of polymer blends with binary distribution of sphere size, (iii) modelling conditions of extreme confinement with the inter-wall distance being as close as possible to sphere diameter (Termonia, 2011), (iv) the simulation of terminally-anchored polymers in complex geometries (Benetatos, 2014;Daoulas et al, 2005Daoulas et al, , 2002Hammer and Kantor, 2014;Maghrebi et al, 2012), (v) analysing the effect of chain stiffness on jamming and phase behaviour, and (vi) the simulation of polymer-colloid mixtures . From the application perspective, dense packings of polymeric systems are particular relevant in a wide range of physical and chemical systems: from colloids and liquid crystals to complex synthetic interfaces and biomolecules.…”
Section: Discussionmentioning
confidence: 99%
“…2(A) is investigated. In this structure the RCLs are formed between monomers (1,20), (3,22), (5,24), (7,26) and (9,28). Thus, the folding pattern of the molecule can be regarded as something like a minimal parallel b-sheet.…”
Section: Single Chainmentioning
confidence: 99%
“…[17][18][19] Analytical evaluations for parallel-stretched polymeric chains with permanent random cross-links showed that increasing the number of cross-links reduces thermal fluctuations 20,21 by reducing the number of allowed configurations. 22 In ref. 23 a kinetic model is introduced to describe the dependence of the maximum force a molecule can sustain on the pulling speed as well as to study the impact of the recovery time on the mechanical response of the system.…”
Section: Introductionmentioning
confidence: 99%